Follicular Helper T Cells in Systemic Lupus Erythematosus - Kim, Sun Jung; Lee, Kyungwoo; Diamond, Betty (Frontiers in Immunology, 2018)
CD4+ follicular helper T (Tfh) cells constitute a subset of effector T cells that participate in the generation of high affinity humoral responses. They express the chemokine receptor CXCR5 and produce the cytokine IL-21, both of which are required for their contribution to germinal center (GC) formation. Uncontrolled expansion of Tfh cells is observed in various mouse models of systemic autoimmune diseases and in patients with these diseases. In particular, the frequency of circulating Tfh is correlated with disease activity and anti-DNA antibody titer in patients with systemic lupus erythematosus (SLE). Recent studies reveal functional diversity within the Tfh population in both humans and mice. We will summarize here the molecular mechanisms for Tfh cell generation, survival and function in both humans and mice and the relationship between Tfh cells and autoimmune disease in animal models and in patients.